Cypermethrin-Induced in vitro Alterations on Oxidative Stress and Quality of Salmo coruhensis Spermatozoa - Kutluyer, Filiz; Kocabas, Mehmet; Erisir, Mine; Benzer, Fulya (Assoc Pharmaceutical Teachers India, 2018)
The use of insecticides has been increasing along with increasing agriculture activities and has caused deleterious environmental impacts. Non-target organisms in particular, including fish, are affected by pesticides. In this work, the impacts of cypermethrin (CYP) on sperm oxidative stress markers and sperm motility were investigated in vitro. The CYP concentrations were 0 mu g L-1 control, ethanol), 1.025 mu g L-1, 2.05 mu g and 4.1 mu g L-1. Lipid peroxidation [Malondialdehyde (MDA)], non-enzymatic antioxidants [glutathione (GSH)] and enzymatic [superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT)] activities in sperm cells were examined for determination of oxidative stress status. Our findings showed that motility and survival of sperm cells significantly decreased with exposure to CYP. Biochemical assays revealed that CAT activity and levels of MDA and, GSH increased in spermatozoa based on CYP concentration while activity of GSH-Px and SOD decreased. Consequently, spermatozoa were highly sensitive to CYP exposure. It can be deduced that CYP has the potential to disrupt sperm quality and to cause to oxidative stress in sperm cells of S. coruhensis.
Keywords: Cypermethrin; Oxidative stress parameters; Salmo coruhensis; Sperm cell